Optimalisasi Pengelolaan Keuangan UMKM Melalui Sistem Pembukuan Terintegrasi Dan Edukasi Perpajakan: Studi Kasus Pada Toko Varietas Mandiri - linda; Johandri Iqbal; Junaidi (LP2M Politeknik Jambi, 2026)
This research aims to optimize the financial management of MSMEs through the application of a Microsoft Excel-based bookkeeping system that is integrated with tax education, with a case study on the Independent Variety Store in Bungo Regency. The main problems studied are manual transaction recording that is prone to errors, low tax understanding, and the lack of use of simple digital tools. The research method uses a case study descriptive approach through observation, interviews, and the development of bookkeeping models in accordance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). The results of the study show that the integrated Excel system is able to improve the efficiency of recording transactions, make it easier to monitor stock, and produce more accurate financial reports. Tax education assistance also increases understanding of NPWP registration procedures and simple tax obligations. The conclusion of this study is that the integration of digital bookkeeping with tax education can be a practical solution for rural areas to improve business sustainability while supporting tax administration compliance.